Apakah Hasangapon, Hagabeon, dan Hamoraon sebagai Faktor Protektif atau Faktor Risiko Perilaku Bunuh Diri Remaja Batak Toba? Sebuah Kajian Teoritis tentang Nilai Budaya Batak Toba - Tience Debora Valentina; Wisjnu Martani (Buletin Psikologi, 2018)
The phrase "Anakhonki do hamoraon in ahu" which means children are parents' treasure, illustrating how precious the children are in Batak Toba family. The perspective of people of Batak Toba, the system of cultural values become the goal and the way of life that passed down from generation to generation that is wealthy (hamoraon), having descendants (hagabeon) and honor (hasangapon). However, along with the high competition of people today, the influence of disposition of personality and low cognitive ability, Batak Toba culture values can be motivating values that encourage Batak Toba teenagers to achieve excellence, as well as the source of pressures that trigger suicidal behavior when the expectations of parents cannot be fulfilled.